Opportunities and Constraints for Climate Adaptation in Regional Water and Land Use Planning - Werners, S E; West, J; Leemans, R; Tabara, J D; Dai, X; Flachner, Z; Neufeldt, H; McEvoy, D; Cots, F; Trombi, G (The Economic, Social and Political Elements of Climate Change, 2011)
Whereas the literature on adaptation is rich in detail on the impacts of, vulnerability to, and constraints of climate adaptation, less is known about the conditions that facilitate adaptation in practice. We examined the constraints and opportunities for adaptation in water and land use planning in three regions: the Guadiana River Basin in Spain and Portugal, the Tisza River Basin in Hungary and western Inner Mongolia in China. We analysed the conditions that either facilitate or constrain adaptation in relation to (1) adaptation actors, (2) adaptation strategies, and (3) adaptation objectives. Many adaptation assessments concentrate on climate impacts and the potential of adaptation strategies. The conditions that enable people to act on adaptation are less studied. Yet these have been identified as particularly important for successfully implementing adaptation. We find that adaptation is enhanced by pilot projects that test and debate new ideas through collaboration between recognized actors from civil society, policy, and science. Promising for adaptation is the integration of (traditional) agro-environmental land use systems that regulate regional climate impacts with new technologies, organizational responsibilities and financial instruments. A key challenge is to create flexible and equitable financial instruments that facilitate benefit and burden sharing, social learning, and that support a diverse set of potentially better adapted new activities rather than compensate for climate impacts on existing activities
Keywords: Adaptation assessment; China; Climate adaptation; EUROPE; Hungary; Land use management; Portugal; Regional water and land use planning; Spain; Water management